TYPES OF MIGRATION: TYPES OF MIGRATION - Metodieva, Tsvetelina (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Migration in Europe is not a new phenomenon. It is estimated that in 1945 there were over 40 million refugees and internally displaced persons in Europe. The military conflicts in the Middle East and North Africa over the last few years, as well as the war in Ukraine, have created a huge wave of refugees heading for the Old Continent.